Venous insufficiency due to chronic traumatic arteriovenous fistula: Two case reports - Rerkasem K. (2014)
Chronic traumatic arteriovenous fistula (AVF) is a rare complication of vascular injury, and few papers have reported on its consequences to the venous system, that is, venous insufficiency. The author has highlighted this problem with 2 case reports in this case presentation. One patient had recurrent chronic ulcer of the left foot. The other patient developed deep vein thrombosis following repair to the large AVF of the right thigh. © 2005 Sage Publications.